Penentuan Kadar Senyawa Aktif Cyanocobalamine Menggunakan Metode Spektrofotometri UV-VIS - Risma Sari; Aisyah Salma Billa (REACTOR: Journal of Research on Chemistry and Engineering, 2020)
Cyanocobalmine is vitamin B12 which is widely used to treat or prevent deficiency (deficiency of vitamins) in various types of preparations. Cyanocobalmine in the 5th edition of Indonesian Pharmacopoeia literature can determine by UV-Vis Spectrophotometric method with water solvent. The purpose of this testing was to determine whether the levels of the active compound Cyanocobalamine from the 3 test parameters. In the description test where the sample tested is the same as the Cyanocobalamine specification, namely, crystal powder is dark red. Hot plate was used to determine drying shrinkage. Shrink drying was 2.25% - 2.75% from the ≤ 12% requirement. The determination of the levels of the active compound of Cyanocobalamine fulfills the requirements, namely 96% - 102.0%. The results of the assay showed that the average level of Cyanocobalamine from 4 samples was 96.02%, which met the standards set by the Pharmacopeia. Indonesia Edition V as a requirement for determining the levels of the active compound Cyanocobalamine.